한국 국가대표 복싱선수들의 체급별 신체조성 및 전문체력 프로파일 - 김광준; 송홍선; 민석기 (Exercise science (Seoul, Korea), 2016)
PURPOSE: The purpose of this study was to analyze the differences of body composition and specific physical fitness by weight category, and examine the reciprocal relationship in national amateur male boxers. METHODS: National amateur boxers were classified into light weight category (LWC, n=14), middle weight category (MWC, n=15) and heavy weight category (HWC, n=14). Subjects were measured for body composition and specific physical fitness: body fat, BMI, maximal strength(bench press, squat), anaerobic power(lower/upper body mean and peak power), isokinetic strength(knee and trunk) and cardiovascular endurance(AT, HRmax, VO2max). One-way repeated ANOVA was used to evaluate the differences between three groups and pearson's correlation analysis was applied to examine the relationship between body composition and specific physical fitness. RESULTS: The results of this study indicated that the HWC was significantly higher in body fat and BMI compare with the LWC and MWC (p<.05). LWC was significantly lower in peak power of upper body compare with the MWC and HWC (p<.05). HWC was significantly higher in power drop rate compare with the LWC (p<.05). On the other hand, HWC was significantly lower in isokinetic trunk flexion, HRmax, VO2max compare with the LWC and MWC (p<.05) while the LWC showed the best level in HRmax and VO2max. There was a significant reciprocal relationship between body fat, BMI and specific physical fitness factors (p<.05). In particular, body fat, squat, mean and peak power showed a significantly relationship with many variables. CONCLUSIONS: Korean national amateur boxers in LWC and MWC showed a great level of VO2max. However, the power endurance of upper body and peak power of lower body estimated to be somewhat low. HWC need to maintain an ideal body fat, and pay focused attention on strengthening the core flexor and cardiovascular endurance. Therefore, if the efficient strategic and specific physical training is planned through this results, it will help the successful preparations for Rio Olympics KCI Citation Count: 8